2007
DOI: 10.2151/jmsj.85.633
|View full text |Cite
|
Sign up to set email alerts
|

Shift and Intensification Processes of the Japan-Sea Polar-Airmass Convergence Zone Associated with the Passage of a Mid-Tropospheric Cold Core

Abstract: A mid-tropospheric mesoscale cold core passed over the Sea of Japan on 14 January 2001 during a cold air outbreak. In association with the passage of the cold core, intensification and northward and southward shifts of the Japan-Sea Polar-Airmass Convergence Zone (JPCZ) were observed. In order to clarify a response of the JPCZ to a change of upper-level environment, the shift and intensification processes associated with the passage of the cold core were studied mainly using a non-hydrostatic cloudresolving mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…This model has been developed at the Hydrospheric Atmospheric Research Center, Nagoya University, Japan (Tsuboki and Sakakibara, 2001;2002), and is used for cold-air outbreaks and snowstorms (Liu et al, 2004;Maesaka et al, 2006;Ohigashi and Tsuboki, 2007).…”
Section: Data and Modelmentioning
confidence: 99%
“…This model has been developed at the Hydrospheric Atmospheric Research Center, Nagoya University, Japan (Tsuboki and Sakakibara, 2001;2002), and is used for cold-air outbreaks and snowstorms (Liu et al, 2004;Maesaka et al, 2006;Ohigashi and Tsuboki, 2007).…”
Section: Data and Modelmentioning
confidence: 99%
“…4f ). The movement and intensification processes of the present JPCZ cloud band have been examined by Ohigashi and Tsuboki (2007).…”
Section: Numerical Model and Experimental Designmentioning
confidence: 99%
“…Nagata (1992) numerically investigated the movement and development of the JPCZ cloud band during the passage of a short-wave trough accompanied by a remarkable cold low. Ohigashi and Tsuboki (2007) clarified the dynamics of the movement and intensification of the JPCZ associated with the upper cold core by using a cloud-resolving model.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most broad cloud bands form in specific locations. Over the Sea of Japan, the broadest cloud bands form along a convergence zone in the western part of the sea (Okabayashi 1969;Yagi et al 1986;Nagata et al 1986;Nagata 1987Nagata , 1991Nagata , 1992Ohigashi and Tsuboki 2007;Eito et al 2010;Ohigashi et al 2012). The convergence zone generating the broadest cloud bands is referred to as the Japan-Sea Polar-Airmass Convergence Zone (JPCZ) (Asai 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Nagata (1992) and Ohigashi and Tsuboki (2007) showed that the JPCZ cloud bands intensified under upper-level mesoscale cold lows. Takeda et al (1982) showed the intensification of isolated snow clouds near a coast.…”
Section: Introductionmentioning
confidence: 99%